Large Increase in Blood Pressure After Extubation and High Body Mass Index Elevate the Risk of Spinal Epidural Hematoma After Spinal Surgery. Issue 13 (1st July 2015) - Yamada, Kentaro; Abe, Yuichiro; Satoh, Shigenobu; Yanagibashi, Yasushi; Hyakumachi, Takahiko; Masuda, Takeshi
<x xml:space="preserve">Abstract</x> Study Design. Matched case-control study. Objective. To identify factors other than a multilevel procedure that increase the risk of symptomatic postoperative spinal epidural hematoma (SEH). Summary of Background Data. Postoperative SEH is a potentially devastating complication of spinal surgery. Previous studies that reported risk factors for postoperative SEH all identified a multilevel procedure as a risk factor, but the other risk factors remain unclear. Methods. Patients who developed postoperative SEH requiring surgical evacuation were identified from database. Each patient was matched with 3 controls who underwent spinal decompression at the same number of levels in the same part of the spine by the same surgeon during the preceding or following year. Multiple logistic regression analysis was performed to identify the risk factors for postoperative SEH to obtain adjusted odds ratios with 95% confidence intervals. Clinical outcomes after evacuation were investigated separately divided with or without severe paralysis or time until the second surgery. Results. Postoperative SEH evacuation was performed after 32 of 8250 (0.39%) spinal decompression procedures. The incidence was significantly higher after thoracic procedures (2.41%) than after cervical (0.21%) or lumbar (0.39%) procedures. Multivariate analysis identified a 50 mm Hg or greater increase in systolic blood pressure after extubation (adjusted odds ratio: 3.22, 95% confidence interval: 1.22–8.51) and higher body mass index (adjusted odds ratio 1.15, 95% confidence interval: 1.01–1.31) as risk factors. Among 14 patients with severe paralysis due to postoperative SEH, those who underwent evacuation within 24 hours of the onset had a significantly better improvement in clinical outcome and Frankel grade than did those after 24 hours. Conclusion. A 50 mm Hg or greater increase in systolic blood pressure after extubation and high body mass index were identified as risk factors for SEH. Appropriate blood pressure control especially at the end of surgery is important for the prevention of postoperative SEH, particularly in obese patients. Level of Evidence: 3